INNOVATION IN BATIK CIPRAT KARANGPATIHAN AS A CREATIVE ECONOMY DEVELOPMENT TO INCREASE SUSTAINABLE COMPETITIVE ADVANTAGE - Yayuk Susilowati; Rochmat Aldy Purnomo; Yeni Cahyono; Asis Riat Winanto; Choirul Hamidah (Universitas Tidar, 2023)
Batik Ciprat Karangpatihan is one of the forms of cultural diversity based on batik products in the Karangpatihan village. In order to empowering disabled people, The Government of Karangpatihan Village collaborate with the Rumah Harapan Mulya personally trained them to make batik, which aims to provide jobs and self-employed income sources for craftsmen with disabilities in Karangpatihan Village. The aim of this study is to explore local economic development, inclusive economy and sustainable economy with a case study of the product Batik Ciprat Karangpatihan. This research uses a qualitative approach using primary data and secondary data. The result of the research, among other things, is the innovation of the media Batik Ciprat Karangpatihan which is a fan, cup and used T-shirt as a development of the usual fabric media. It can be concluded that the new innovation potential of Batik Ciprat Karangpatihan from the development of the local economy is by exploiting the potential of the corn grove region to filter Batik waste, the inclusive economy is empowering the disabled community and the local poor population, and the sustainable economy with the presence of development on the batik media and environmentally friendly that can then increase the income of the public by making the creation of batik with new fashion media, T-shirts, cups, and fans.